2015
DOI: 10.1007/s00220-015-2461-2
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Field Theories with Polynomial Shift Symmetries

Abstract: We continue our study of naturalness in nonrelativistic QFTs of the Lifshitz type, focusing on scalar fields that can play the role of Nambu-Goldstone (NG) modes associated with spontaneous symmetry breaking. Such systems allow for an extension of the constant shift symmetry to a shift by a polynomial of degree P in spatial coordinates. These "polynomial shift symmetries" in turn protect the technical naturalness of modes with a higher-order dispersion relation, and lead to a refinement of the proposed classif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 47 publications
1
106
0
Order By: Relevance
“…40) 41) and yield the primary first class constraints [38] 43) with exactly the same equal-τ Poisson brackets (3.7) of the non-vibrating case. The canonical action is …”
Section: Jhep02(2017)049mentioning
confidence: 89%
See 1 more Smart Citation
“…40) 41) and yield the primary first class constraints [38] 43) with exactly the same equal-τ Poisson brackets (3.7) of the non-vibrating case. The canonical action is …”
Section: Jhep02(2017)049mentioning
confidence: 89%
“…An infinite set of non-central extensions in the algebra of conserved charges is also obtained. If should be emphasized that among the symmetries there is an infinite set of polynomial shift symmetries [41,42]. The presence of polynomial shift symmetries has been noticed in Galileon theories [43].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…[7,8], we showed that this type A-B dichotomy is further refined into two discrete families, labeled by a positive integer n: type A n NG modes are described by a single scalar with dispersion ω ∼ k n (and dynamical critical exponent z ¼ n), while type B 2n modes are described by a canonical pair and exhibit the dispersion relation ω ∼ k 2n (and dynamical exponent z ¼ 2n). These two families are technically natural, and therefore stable under renormalization in the presence of interactions [7].…”
mentioning
confidence: 98%
“…Much progress in SSB has also been achieved in the nonrelativistic cases, where the reduced spacetime symmetries allow a much richer behavior, still very much the subject of active research (see, e.g., Refs. [2][3][4][5][6][7][8] and the references therein). Important novelties emerge already in the simplest case of theories in the flat nonrelativistic spacetime R Dþ1 [covered with Cartesian coordinates ðt; xÞ, x ≡ ðx i ; i ¼ 1; …; DÞ] and with the Lifshitz symmetries of spatial rotations and spacetime translations.…”
mentioning
confidence: 99%
See 1 more Smart Citation